Tutoria: Supporting Good Practices for Providing Written Educational Feedback - Pontual Falcão, Taciana; Oliveira, Verenna; Souza, Samuel; Fiorentino, Giuseppe; Rodrigues Neto, José; Galdino, João Victor; Alves, Gabriel; Ferreira Mello, Rafael (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2022)
In learning processes, feedback given by instructors is essential to guide students and help them improve from their mistakes. However, in higher education, instructors feel unable to give quality and timely feedback due to work overload and lack of time. As online classes became dominant due to the Covid 19 pandemic, and with increasing numbers of students per class, giving feedback beyond grades is even less realistic. Software tools to support feedback processes typically focus on automatic messages, which is not ideal as they lack personalization. Aligned with more recent research which suggests a broader perspective on the feedback process, we propose a software tool to help instructors construct quality written feedback efficiently. Through iterative user-centered design and applying artificial intelligence techniques, we developed functionalities that support correction of activities and allow building personalized written feedback, thus allowing instructors to give quality feedback to large groups, within realistic time frames.